Virtual post-soviet space: Russian language and transnational communities - Yelenevskaya, Maria; Protassova , Ekaterina (Universitas Ahmad Dahlan, 2023)
This article explores linguistic and cultural ties in the informal Russian-speaking communities outside the Former Soviet Union (FSU). We employ qualitative methods, such as internet discourse monitoring, ethnographic observations, content and thematic analysis, and language assessments to examine a complex interplay between language, migration, and identity. We explore the role of a common language and cultural background in shaping the relationships and activities within the communicative sphere of Russian-speaking immigrants. The findings reveal that since the Soviet times, the FSU citizens have developed distrust of official channels and learned to rely on informal social networks. Sometimes immigrants activate their old friendships from study times, sometimes diasporans meet at language courses where they learn the local language, sometimes they get to know each other through children on the playground or during parents’ meetings at school. The virtual fora and mutual interests, aspirations for their children’s future, and attitudes toward political problems may unite or divide people who have left their home country. Overcoming difficulties of the first period of acculturation, acquiring proficiency in the local language/s, becoming familiar with the culture, and expanding social networks beyond the co-ethnics—all of these make permanent resettlement more realistic and desirable. Most often in each individual case there is a whole constellation of push factors that motivated people to migrate, and it is this constellation that distinguishes migrants from Russia and CIS countries from other groups. Although the very notion of diaspora has undergone major changes, migrants still tend to keep together with co-ethnics, at least in the first stages of life away from home. The transnational relations may be motivated by economic interests and are viewed as social capital. In many cases they are vehicles of solidarity and warmth, yet in the periods of political conflict they may also reflect distress, animosities and even mutual hate.